Education in the Digital World: From the Lens of Millennial Learners - Cenita, Jonelle Angelo S.; De Guzman, Zyra R. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – The objective of this study is to determine Education in the Digital World: from the lens of millennial learners. This also identifies the cybergogical implications of the issue with digital education as seen through the lens of the outlier. Method – This study uses a mixed-methods sequential explanatory design. A quantitative method was employed during the first phase and the instruments of the study were distributed using google forms. The survey received a total of 85 responses and the results were analyzed using descriptive methods. Following up with a qualitative method, during the second phase the outliers were interviewed, and the results were analyzed using thematic analysis. The results of the mixed methods were interpreted in the form of cybergogical implications. Results – The digital education from the lens of millennial learners in terms of the Benefits of E-Learning and Students’ Perceptions of E-Learning received an overall mean of 3.68 which was verbally interpreted as "Highly acceptable". The results reveal that millennial learners' perceptions of digital education are influenced by the convenience in time and location, the fruit of collaboration using online interaction, the skills and knowledge they will acquire using digital resources, and the capability of improving themselves for the future. Conclusion – E-learning significantly improves the quality of the learning and teaching process. Millennial learners with different learning styles and speeds were addressed by its usability and portability features. Millennial learners were able to adopt and learned how to use e-learning. Also, since it is self-paced learning, it allows them to study on their own time and schedule since e-learning can be accessed anytime and anywhere. However, the technological resources of the learners should be considered in the implementation of e-learning. Recommendations – The utilization of e-learning as a medium of instruction for millennial learners. Research Implications  – The findings can be used by the institution to create guidelines, procedures, and policies for successfully implementing digital education or E-Learning.